HGG-35. Radiation Induced High Grade Gliomas: A Single Center Experience. (3rd June 2022) - Joshirao, Mrinal; Sait, Sameer Farouk; Bouvier, Nancy; Hill, Katherine; Khakoo, Yasmin; Kramer, Kim; Gilheeney, Stephen; Wolden, Suzanne; Nolan, Craig; Schaff, Lauren; Rosenblum, Marc; Bale, Tejus A; et al.
Abstract: INTRODUCTION: Patients receiving cranial radiotherapy (RT) are at risk for a subsequent radiation-induced glioma (RIG). RIGs are rare, generally develop with a latency of 2 years to several decades, display high-grade histology and an aggressive clinical course with poor prognosis. METHODS: We retrospectively analyzed patients with a diagnosis of RIG seen at our institution from 2001-2021, analyzing clinical, histological, molecular, and genetic characteristics. RESULTS: Twenty-one patients (n=15 male) with a history of ALL (n=6), medulloblastoma (n=5), germ cell tumors (n=4), or other (n=6) diagnosed at a median age of 8.3 years (range 1.6 to 36.4) were identified. Median age at RIG diagnosis was 18 years (range 7.8 to 66.9). Prior RT was focal+craniospinal (n=7), whole brain (n=5), total body (n=3), focal (n=1), or unknown (n=5). Median radiation dose received was 2, 340 cGy (range 1, 200 to 5, 400). The median time from RT to RIG diagnosis was 7.7 years (range 1.6 to 23.8). All RIGs were histologically high grade (WHO Grade III or IV). Immunohistochemistry did not reveal IDH(R132H) (n=9) or H3K27M (n=8) in any tumor. Some tumors demonstrated loss of expression of ATRX (1/9) and/or H3K27me3 (3/6), and/or strong diffuse expression of p53 (0/3). Targeted panel sequencing (n=10) revealed recurrent somatic alterations including CDKN2A/B, PDGFRa/KIT/KDR, TEK, MTAP, ATM and NF1. Germline alterations were detected in 4/12 patients (pathogenetic variants in ATM, CHEK2, HOXB13 and NF1). With median follow-up of 4.5 years, two-year PFS and OS for the cohort (n=20) were 10% and 44% respectively. Two patients (with anaplastic oligodendroglioma and anaplastic astrocytoma) are alive without progression 5.4 and 13.6 years after diagnosis following surgery, RT and chemotherapy. CONCLUSION: Although RIGs are associated with a poor prognosis, they are not always fatal. Our findings suggest aggressive therapy should be considered for these patients.